(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
تتناول هذه الدراسة صوت الجسد المحروم، وأثر ه في النفس، في شعر تأبط شرّاً، من خلال النصوص الشعريّة التي ينبثق منها صوت الجسد، في حالات الحرمان المتعدِّدة، والتي تعكس إيماءات هذا الجسد المعنوية وتصوِّر أفعاله الموشية بفقد مقوِّمات الوجود. ويقوم البحث على أربعة محاور رئيسة، تبيِّن حرمان الجسد والنفس من أسباب الحياة الآمنة، والوجود الإنساني؛ وهي: الجوع، والعذاب، والغربة، والقلق. يعالج المحور الأول حرمان الجسد مدّخراته الغذائية الحرورية اللاّزمة لاستمرار الفعل، ومقاومة الجسد ويبيِّن أنّ فقدها يودي بالجسد إلى الضّعف والهُزال. أمّا المحور الثاني فيعرض لحرمان الجسد أسباب الراحة والاستقرار؛ ممثّلاً بالعذاب النفسي والجسدي المعيش، عبر القمع، والقهر، واضطهاد الذات. ويدرس المحور الثالث حرمان الجسد الانتماء إلى وسطه المحيط، وحرمان النفس الحسّ بالأمن والأمان الباديين في حياة الصعلكة، التي قادت الجسد، والنفس إلى الإحساس بالغرْبة. وينطلق المحور الرّابع من حرمان الجسد أمنه وطمأنينته، في معايشةِ القلق الدائم، والخوف المستمرّ. وتحاول هذه الدِّراسة تسليط الضّوء على العلاقة الوطيدة بين الجسد والنفس، مبيِّنة أثر كلّ منهما في الآخر. وتبرز الخاتمة النتائج المستخلصة، موضِّحة الأثر المتبادل بين النفس والجسد، في مظاهر الحرمان، في شعر تأبَّط شرّاً. This study dials with the sound of deprived body and its effect on the soul in the poetry of Ta’abbata Sharran, through the poetic texts from which the sound of the body emerges in several cases of deprivation which reflect the body’s spiritual hints and imagining of its acts, signaling loss of means of existence. The research is essentially based on four pivots, showing the deprivation of the soul and body of causes of peaceful life and human existence which are hunger agony alienation and anxiety. The first pivot deals with the deprivation of the body of its contents of thermal charges necessary for continuity of action and resistance of the body while its loss leads to a thin and weak body. The second pivot shows the causes of the body’s deprivation of the means of stability and comfort represented by daily life psychological and physical agony through compulsion repression and self-oppression. The third pivot studies the deprivation of the body of its affiliation to its atmosphere and the deprivation of the soul of the sense of security and safety shown in the outlaw life which led the body and soul to the sense of alienation. The fourth pivot starts out from the body deprivation of its peace and comfort in living with the perpetual anxiety and continuous fear. This study attempts to cast the light on the strong relationship between the body and soul showing the effect of each on the other. The end presents results showing the mutual effect between the body and soul in the aspects of deprivation in the poetry of Ta’abbat Sharran.